BaBi(SeO3)2Cl: a new polar material showing high second-harmonic generation efficiency enhanced by constructive alignment of chloride ions. Issue 47 (18th November 2015) - Geng, Lei; Li, Qiang; Meng, Chang-Yu; Dai, Kai; Lu, Hong-Yan; Lin, Chen-Sheng; Cheng, Wen-Dan
Abstract : A novel polar material oxychloride BaBi(SeO3 )2 Cl with high SHG efficiency (∼16 × KDP) has been synthesized and characterized. Abstract : The novel oxychloride BaBi(SeO3 )2 Cl with polar crystal structure was first synthesized by using hydrothermal method at a mild temperature of 200 °C. It crystallizes in the orthorhombic Cmc 21 (36) space group with cell parameters of a = 5.2804(2) Å, b = 20.0535(9) Å, c = 6.9070(3) Å, V = 731.39(5) Å 3, and Z = 4. The compound features a two-dimensional [Bi(SeO3 )2 Cl] 2− anionic layer structure stacking along the crystallographic b -axis direction. Within the [Bi(SeO3 )2 Cl] 2− layer, BiO4 quadrangular pyramids bridge two types of Se(1)O3 and Se(2)O3 triangular pyramid through corner-sharing manner into a [Bi(SeO3 )2 ] − chain. The [Bi(SeO3 )2 ] − chains are aligned along c -axis direction with chloride ions adjacent to bismuth cations, and the 2D [Bi(SeO3 )2 Cl] 2− forms. As a consequence, local dipole moments of the building block layers are arranged in a constructive fashion, which is favourable to enhance the second-order nonlinear properties of materials. Powder Kurtz–Perry method was utilized to evaluate the second-harmonic generation (SHG) efficiency, indicating a strong SHG effect (about 16 times that of KH2 PO4 (KDP) reference). More excitingly, BaBi(SeO3 )2 Cl can achieve type I phase-matching, which make the compound feasible for practical applications. In addition, first-principles density functional theory (DFT) calculations were also performed to illustrate the relationships between crystal structure and optical properties.